Time Domain Analysis of Sound Signals for Bearing Damage Identification - Muhammad Aswin; ING Wardana; Yudy S. Irawan; Hadi Suyono (IAES Indonesia Section, 2014)
Time domain analysis requires less computational time compared to the frequency domain. Analysis is performed directly on the signal without any conversion at all. This paper describes high-frequency signal analysis on sound produced by rotated bearing. Three bearing conditions - normal, damaged, and badly damaged - was chosen to obtain the characteristics of high frequency sound. From the entire spectrum of the recorded sound, the higher frequency range looks very different for the three conditions bearing. Phisically, more damage rotated bearing, the disturbance sound heard more loudly. Bearings were rotated at various rpm, from low to high, to ensure the similarities and differences in characteristics. Average energy and standard deviation were calculated as bearing damage indication.